18F-Prostate-Specific Membrane Antigen and 18F-Fluorodeoxyglucose PET/CT Unmasked the Characteristics of Prostate Lymphoma: A Case Report and Literature Review - Jiang, Fan; Fan, Junjie; Liang, Hua; Duan, XiaoYi; He, Dalin; Wu, Kaijie (Frontiers in Medicine, 2022)
Prostate lymphoma (PL) is rarely observed and may be concurrently presented with prostate adenocarcinoma. Moreover, the appearance of PL on conventional imaging was similar with prostate adenocarcinoma. Thus, most of PL was diagnosed through prostate biopsy, or accidentally found in the specimens of surgery. Prostate-specific membrane antigen (PSMA) PET/CT has improved the management of prostate adenocarcinoma. While, question regarding whether it benefits to reveal the characteristic of PL is unknown.A 32-year-old male presented with worsening dysuria for 1 month, and the prostate-specific antigen was normal. While the pelvic MRI showed a mass in the prostate and multiple enlarged lymph nodes in the bilateral inguinal. Then, the diagnosis of prostate adenocarcinoma was considered, but the serum PSA was normal and he was so younger. So, 18F-PSMA PET/CT was then performed to further reveal the characteristic of lesion and guide biopsy. However, there was no abnormal PSMA uptake in the lesion of the prostate and lymph nodes of pelvic cavity and bilateral inguinal area. While these lesions presented with increased glucose metabolism on FDG PET/CT, and the prostate biopsy was then performed. The PL was confirmed based on the results of the histopathologic examination, and the patient subsequently received systemic chemotherapy plus radiotherapy. Fortunately, the symptom and the lesions were completely disappeared after radiotherapy. The clinical symptoms of PL are atypical, and prostate lymphoma and adenocarcinoma may be concurrently presented. Moreover, distinguish PL from prostate adenocarcinoma based on the appearance of conventional imaging was difficult. As opposed to the prostate adenocarcinoma, a high FDG-avidity and low PSMA uptake by lymphoma either in prostate or metastases. PSMA PET/CT combined with FDG PET/CT non-invasively identify the characteristics and origin of PL.